The impact of transformational leadership practices on employee satisfaction at Pelabuhan Tanjung Pelepas (PTP) / Noor Hanisah Adnan - Adnan, Noor Hanisah (Faculty of Business and Management, 2016)
A leader and employees play an important roles and responsibilities to the success of the organization. A previous study has shown that leadership styles could give impact toward the satisfaction of employee. Transformational leadership was found to be more influenced compare to transactional leadership. Thus, this study aims to examine the relationship between transformational leadership styles toward employee satisfaction at Pelabuhan Tanjung Pelepas Sdn. Bhd. (PTP). A total of 110 set of questionnaires were distributed to respondents which are the employee of PTP. The Correlations and Regression analysis were conducted to test the hypothesis. Results indicated that idealized influences, intellectual stimulation and individualized consideration do have an impact on employee satisfaction. Based on the results, the recommendation and relevant direction for future studies are also discussed.